A short treatise on the metaphysics of tsunamis - Dupuy, Jean-Pierre (Studies in Violence, Mimesis, and Culture, 2015)
Intro -- Contents -- A Note on the Translation -- Acknowledgments -- Chapter 1. Genesis -- Chapter 2. From Lisbon to Sumatra -- Chapter 3. The Naturalization of Evil -- Chapter 4. The Problem of Future Catastrophe -- Appendix. Japan, 2011 -- Notes -- Index.